2012
DOI: 10.1063/1.4730699
|View full text |Cite
|
Sign up to set email alerts
|

Seismic wave propagation modeling in porous media for various frequencies: A case study in carbonate rock

Abstract: A finite volume method for the solution of fluid flows coupled with the mechanical behavior of compacting porous media AIP Conf.Abstract. Seismic wave parameter plays very important role to characterize reservoir properties whereas pore parameter is one of the most important parameter of reservoir. Therefore, wave propagation phenomena in pore media is important to be studied. By referring this study, in-direct pore measurement method based on seismic wave propagation can be developed. Porosity play important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Some studies in Indonesian carbonate characteristics have been reported by some authors, i.e. [1]- [5]. There are some possibilities in the uniqueness of the Indonesian carbonate characteristics, especially in Java, due to high geothermal heat flow which produced by either volcanism activity or fault activity, see [6] This research may reveal the uniqueness of Indonesian carbonate due to the CO2 injection characteristics.…”
Section: Introductionmentioning
confidence: 83%
“…Some studies in Indonesian carbonate characteristics have been reported by some authors, i.e. [1]- [5]. There are some possibilities in the uniqueness of the Indonesian carbonate characteristics, especially in Java, due to high geothermal heat flow which produced by either volcanism activity or fault activity, see [6] This research may reveal the uniqueness of Indonesian carbonate due to the CO2 injection characteristics.…”
Section: Introductionmentioning
confidence: 83%
“…Our emphasis is to narrowing down the observation and measurement scale so that the influence of the pore structure to the seismic propagation, and particularly seismic velocity can be seen accurately. The wave simulation is based on the finite difference modelling for acoustic propagation which involves the use of neural network for generating velocity and density profile [3,4]. In addition, Kuster-Toksoz theoretical model and Wyllie time average [5] were applied by using the input from pore quantification and constituent fraction in order to give the velocity estimates in thin section scale.…”
Section: The Thin Section Rock Physics: Modeling and Measurement Of Smentioning
confidence: 99%
“…The second sample (Figure 1b), is the sample that has the mouldic ooid shape pore spaces and composed of mono-mineral matrix of calcite. Quantification of the pore structure was performed by using image analysis technique and the aid of the artificial neural network for segmentation and constituent fraction estimation task [3,4]. The thin section images that originally are in RGB color space need to be transformed into binary in order to enable the pore quantification easily.…”
Section: Pore Structure Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al reported the Love wave propagation in double-porosity media (Dai and Kuang 2006) and concluded that Love wave speed is higher in single-porosity layer/half-space than in the double-porosity medium, while the attenuation of Love waves is lower in single-porosity layer/half-space than in double-porosity medium. Nurhandoko et al (2012) have done a case study and observed the seismic wave propagation in porous media (carbonate rock) for various frequencies.…”
Section: Introductionmentioning
confidence: 99%